Positive Charge on Porphyrin Ligand and Nature of Metal Center Define Basic Physicochemical Properties of Cationic Manganese and Iron Porphyrins in Aqueous Solution - Franke, Alicja; Scheitler, Andreas; Kenkel, Isabell; Lippert, Rainer; Zahl, Achim; Balbinot, Domenico; Jux, Norbert; Ivanovic-Burmazovic, Ivana (Inorganic Chemistry, 2019)
Recently, comprehensive studies on positively charged manganese porphyrins show that these compounds, known for their superoxide dismutase (SOD) mimetic ability, can be equally reactive toward a broad array of other redox active molecules of biological relevance present in a cellular milieu. In this context, the examination of some fundamental aspects of physicochemical behavior of metalloporphyrins behind their rich aqueous chemistry is believed to provide a valuable basis for the understanding of newly observed biological effects of these compounds in vivo and throw more light on a potential use of common SOD porphyrin mimetics for other redox active cellular targets in order to earn desirable therapeutic effects. Herein, we present versatile characteristics of highly positively charged Mn(P) and Fe(P) porphyrins (with up to +9 and +8 overall charge, respectively) with regard to their acid-base equilibria, metal coordination sphere, water-exchange dynamics, redox properties, and substitution behavior toward selected ligands. For the purpose of these comparative studies, we synthesized for the first time a 9-fold cationic manganese(III) porphyrin. The findings reported in this study enabled highlighting the most important similarities and differences characterizing the aqueous chemistry of positively charged manganese and iron porphyrins and, therefore, outlining the potential factors which can affect the intimate underlying mechanism behind the redox cycling of these metalloporphyrins.
CRIS-Team Scopus Importer:2019-08-30